Tuberous Sclerosis Complex: Early Screening and Infant Outcome in NICU. (7th March 2021) - Su, Yajie; Wei, Qiufen; Wan, Jing; Li, Long
Abstract: Objective: We describe the clinical and genetic features, drug use and neuropsychiatric disorders of infants diagnosed with tuberous sclerosis complex (TSC) within 3 months of age at a neonatal intensive care unit (NICU) to better understand the different outcomes from early screening. Methods: In this retrospective study, we consisted of 42 infants with a definitive TSC diagnosis by genetic criteria (TSC1  =  8, TSC2 =  34). The different phenotypes and outcomes between patients with TSC1 and TSC2 mutations were analyzed. Results: The most common initial presenting features of TSC were cortical tubers on magnetic resonance imaging (50%), hypomelanotic macules on skin (47.61%) and spasm (42.85%), when they were diagnosed. Following disease progression to time of follow-up 1 year later, we found that the rate of epilepsy increased from 42.85% to 75.61% and that of cardiac rhabdomyoma increased from 28.57% to 43.9%. The median age at first presentation was 7.84 ± 1.88 months. We also found that 54.83% of patients on medication were seizure free for over 1 year, and that 43.9% of patients have intellectual disability. In total, 42 variants of TSC were detected, including 12 novel variants. We found no evidence of an association between different clinical features and their outcomes among patients with different gene mutations. Conclusion: Early diagnosis of TSC in NICU opens a window of opportunity for early, more effective treatment of epilepsy as well as reduces the risk of neurological conditions.